An effective learning application for autism spectrum disorder (AELA) - Nur Aqilah, Osman (2019)
For the time being, there are many autism applications had been developed for Android and iOS users which they can be installed in Play Store and Apple store. Those applications are to help the autism kids and also as an alternative for full time working parent and middle low-cost income parent. However, those existing applications that has been developed is very limited in learning module. So, their parent needs to download more autism application to give more learning exposure but at the same time it will affect their phone storage. Furthermore, there are some of the module that parents need to pay for their autism kids to continue the learning process. The existing application for learning does not only developed in education platform but also some of them are developed in gaming platform. This will make the autism kids not only learning but at the same time having fun using the application. Apart from that, the existing application does not have activity or quiz to measure the kids understanding and progression instead of they should have a scoring. Therefore, this project will be designed to improve the existing application that are existed in the market. An Effective Learning Application for Autism Spectrum Disorder (AELA) is one of the learning applications via gaming platform. It will be focus on developing a mobile application in education for autism kids which have variety of module to make the kids more understanding. The objective of this project is to study the related autism application and find the idea to improve it, to developed a learning module mobile application via game for autism kid and to evaluate the functionality of the purpose mobile application for android user. Besides that, the methodology that used in AELA development is Rapid Application Development which meet the overall fast phase to build the application that can be use by autism kids. AELA is developed by using Unity platform. This application helps autism kids increase their knowledges by having a variety of modules. Furthermore, they are not only learning but at the same time having fun using the application. AELA application is successfully implemented and result of UAT can be accepted.